Artificial Intelligence and Robotics - Lu, Huimin; Xu, Xing.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book highlights selected papers presented at the 2nd International Symposium on Artificial Intelligence and Robotics 2017 (ISAIR2017), held in Nakamura Centenary Memorial Hall, Kitakyushu, Japan on November 25-26, 2017. Today, the integration of artificial intelligence and robotic technologies has become a topic of growing interest for both researchers and developers from academic fields and industries worldwide, and artificial intelligence is poised to become the main approach pursued in next-generation robotics research. The rapidly growing number of artificial intelligence algorithms and big data solutions has significantly extended the number of potential applications for robotic technologies. However, it also poses new challenges for the artificial intelligence community. The aim of this symposium is to provide a platform for young researchers to share the latest scientific achievements in this field, which are discussed in these proceedings.
Identification of the Conjugate Pair to Estimating Object Distance: An Application of the Ant Colony Algorithm.-Design of Palm Acupuncture Points Indicator --  Low-rank Representation and Locality-constrained Regression for Robust Low-Resolution Face Recognition -- Face Recognition Benchmark with ID Photos -- Scene Relighting using a Single Reference Image through Material Constrained Layer Decomposition -- Applying Adaptive Actor-critic Learning to Human Upper Lime Lifting Motion -- A Demand-based Allocation Mechanism for Virtual Machine -- A Joint Hierarchy Model for Action Recognition Using Kinect -- QoS-Based Medical Program Evolution -- An Improved 3D Surface Reconstruction Method based on Three Wavelength Phase Shift Profilometry -- The Research on the Lung Tumor Imaging based on the Electrical Impedance Tomography -- Combining CNN and MRF for Road Detection -- The Increasing of Discrimination Accuracy of Waxed Apples based on Hyperspectral Imaging Optimized by Spectral Correlation Analysis -- A Diffeomorphic Demons Approach to Statistical Shape Modeling.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence